PENGARUH PENGGUNAAN MEDIA MAGIC BOX TERHADAP KEMAMPUAN LITERASI AWAL ANAK USIA 5-6 TAHUN DI TK KEMALA BHAYANGKARI 07 CABANG GOWA - Fadillah.M, Nur; Syamsuardi; Hasmawaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using the Magic Box media on the early literacy skills of 5- to 6-year-old children at Kemala Bhayangkari 07 Kindergarten, Gowa Branch. This study employed a quantitative approach using a quasi-experimental design. The study population consisted of 30 children; purposive sampling was used to select 15 children for the experimental group and 15 children for the control group. Data collection techniques included observation, tests (pretest and posttest), and documentation. Data analysis utilized descriptive and inferential statistics, including paired-sample t-tests and independent-sample t-tests, conducted using SPSS 32. The results indicated that the early literacy skills of children in the experimental group were higher than those in the control group. The average increase in the experimental group was 13.46, while that of the control group was 7.73. The results of the statistical test showed a significance value (two-tailed) of 0.000 < 0.05; therefore, H₀ was rejected and H₁ was accepted. Thus, the use of the Magic Box media has a significant effect on the early literacy skills of 5- to 6-year-old children at Kemala Bhayangkari Kindergarten 07, Gowa Branch.